Challenges in the management of acute intermittent porphyria with recurrent attacks during pregnancy: A case report. Issue 12 (30th July 2020) - Vassiliou, Daphne; Lempessi, Chariklia; Harper, Pauline; Sardh, Eliane
Abstract: In cases of recurrent attacks of acute porphyria during pregnancy, prophylactic administration of heme arginate should be considered. Clinical and biochemical monitoring of the disease and a close collaboration with a porphyria center are crucial. Abstract : In cases of recurrent attacks of acute porphyria during pregnancy, prophylactic administration of heme arginate should be considered. Clinical and biochemical monitoring of the disease and a close collaboration with a porphyria center are crucial.